The law officer's pocket manual - Miles, John G.; Richardson, David B. 1935-; Scudellari, Anthony E. (Routledge, 2020)
The Second Circuit reaffirmed the principle that prolonging a traffic stop is not unconstitutional if the reason is supported by reasonable suspicion. Annually updated since 1972, The Law Enforcement Pocket Manual, provides police officers, criminal justice practitioners, and students with historical and social context for their role in criminal justice and the guidelines that should be followed in day-to-day policing activities. Routledge offers tiered discounts on bulk orders of 5 or more copies: For more information, please visit: https://www.routledge.com/collections/16268